1988
DOI: 10.1007/bf01807284
|View full text |Cite
|
Sign up to set email alerts
|

Association of breast fluid coloration with age, ethnicity, and cigarette smoking

Abstract: Nipple aspirates of breast fluid (NAF) occur with different colorations (colorless, white, pale yellow, dark yellow, brown, green, and black). Increasing concentrations of cholesterol, cholesterol 5,6-epoxides, estrogens, and fluorescent products of lipid peroxidation have been positively associated with the dark colorations (dark yellow, brown, green, and black). Because of the absence of data on these variations in breast fluid coloration, we made an exploratory study of their possible associations with age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…NAF contains a large variety of substances, including hormones, growth factors, and mutagens, and is especially high in protein and lipids (1,(7)(8)(9)(10)(11)(12)(13)(14)(15). Intraindividual and interindividual variation in NAF composition is large (16)(17)(18), but the biological basis and the consequences of this variation are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…NAF contains a large variety of substances, including hormones, growth factors, and mutagens, and is especially high in protein and lipids (1,(7)(8)(9)(10)(11)(12)(13)(14)(15). Intraindividual and interindividual variation in NAF composition is large (16)(17)(18), but the biological basis and the consequences of this variation are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that this is primarily a result of the association of deeper colorations with older ages. In a prior study [9], we found the proportion of NAF of darker coloration progressively increased from approximately 20% in women aged 20-30 years to about 50% in women aged 50-60 years. It is likely that the results of Chotiner et al [6] relating lactose and color may be due to age differences rather than to any direct biochemical interrelationships.…”
Section: Discussionmentioning
confidence: 89%
“…These findings indicate that the adult 'resting' breast actively secretes breast-specific substances in a high proportion of nonpregnant adult women. More recently, we reported that NAF of deep yellow, brown, green, or black colorations increase in frequency with advancing age and contain significantly higher mean concentrations of cholesterol, estrogen, and other fat soluble compounds than do colorless, white, or pale yellow colored NAF samples [8,9]. This finding suggests that the degree of retention or impaired reabsorption of breast secretion can be inferred from its coloration.…”
Section: Introductionmentioning
confidence: 89%
“…Starting from the evidence that high fat intake is associated with increased breast secretory function [28,63], the enhanced secretion/accumulation of lipids in NAF might increase the risk of BC through the exposure of the breast epithelium to carcinogens; in fact, oxidized cholesterol metabolites (such as cholesterol-5,6-epoxides and cholestane-3 beta, 5alpha, 6 beta-thriol) are significantly elevated in NAF of women at increased risk for BC [17,46]. These cholesterol oxides found in breast fluids could exert genotoxic effects on the breast epithelium, and increased levels of cholesterol b-epoxide have been associated with the presence of increasing atypia in the exfoliated cells, proning women to BC progression [18,50]. Interestingly, higher dietary intake of saturated Fig.…”
Section: Role Of Nutrients In Nipple Aspirate Fluids: Effects On Breamentioning
confidence: 99%